Lo smarrimento come inizio in alcuni testi di Giuseppe Culicchia - Puto, Małgorzata (Romanica Silesiana, 2020)
The aim of the present article is to analyze the relationship between the city and the protagonists of Giuseppe Culicchia’s texts. The methodological perspective is that of cultural anthropology, in particular the concept of mente locale, discussed by Franco La Cecla. Mente locale, as a relationship between space and human mind, is vital in the act of getting lost in space (perdersi), which leads to getting to know it (orientarsi) and finally initiating the profound relationship based on emotivity. Culicchia’s texts are set in Turin, and the study points out the different ways of perception of the city. The analyzed texts represents the gradual acquisition of knowledge about the city that corresponds to the theoretical thesis that is how the anthropology of space and place illustrates the conceptual and material dimensions of space which is central to the production of social life, bringing classics of cultural anthropology together with new theoretical approaches.